PENERAPAN MODEL PROBLEM BASED LEARNING PADA MATERI SISTEM REPRODUKSI UNTUK MENINGKATKAN LITERASI SAINS - Darawerti, Luthfia Kinanthi; Astriani, Dyah (PENSA E-JURNAL: PENDIDIKAN SAINS, 2026)
The background of this research is the low level of scientific literacy among junior high school students, a crucial competency in the 21st century. Based on the results of the 2022 PISA survey, the average scientific literacy score of Indonesian students was only 383 points, and still below the international average. This study aims to improve students' scientific literacy skills through the application of the Problem Based Learning (PBL) model based on Socio-scientific Issues (SSI) articles on the human reproductive system, analyzed by gender. The background of this research is the low scientific literacy among junior high school students, which is an essential competency in the 21st century. This quantitative research used a one-group pretest-posttest design involving 35 students of class IX-C at SMPN 1 Gampengrejo, Kediri Regency. Data were collected through observation and scientific literacy tests covering competencies such as explaining phenomena, evaluating investigations, and interpreting evidence. Data were analyzed by comparing pretest and posttest scores, calculating normalized gain (N-gain), and testing significance using the Mann–Whitney test. The results showed that (1) learning implementation reached 100%, indicating that all activities were carried out as planned, and (2) students’ scientific literacy improved significantly with an average N-gain of 0.56 (moderate category). Male students showed a slightly higher improvement compared to female students. These findings suggest that SSI-based PBL is an effective learning approach to enhance students’ scientific literacy on the topic of the human reproductive system.